National Hispanic Democratic Caucus Reception at Miles, Sears and Eanni - Watkins, Howard::::::::: (1988)
Attorney General John Van de Kamp, Congressman Estevan Torres; looking on Ralph Nunez, Leo Gallegos, and Richard Watters